2012
DOI: 10.1007/s13238-012-2090-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of YB-1 enhances production of murine leukemia virus vectors by stabilizing genomic viral RNA

Abstract: Murine leukemia virus (MLV)-based retroviral vectors iswidely used for gene transfer and basic research, and production of high-titer retroviral vectors is very important. Here we report that expression of the Y-box binding protein 1 (YB-1) enhanced the production of infectious MLV vectors. YB-1 specifically increased the stability of viral genomic RNA in virus-producing cells, and thus increasing viral RNA levels in both producer cells and virion particles. The viral element responsive to YB-1 was mapped to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…YBX1 also binds hairpin-loops in a murine retrovirus, leading to stabilization of the viral RNA genome and increased particle production (Bann, Beyer, & Parent, 2014). YBX1 binding of viral RNA also increases production of other retroviruses, including HIV (Bann et al, 2014;W. Li, Wang, & Gao, 2012;Mu, Li, Wang, & Gao, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…YBX1 also binds hairpin-loops in a murine retrovirus, leading to stabilization of the viral RNA genome and increased particle production (Bann, Beyer, & Parent, 2014). YBX1 binding of viral RNA also increases production of other retroviruses, including HIV (Bann et al, 2014;W. Li, Wang, & Gao, 2012;Mu, Li, Wang, & Gao, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Y-box binding protein 1 (YBX1) is a transcription/ translation factor involved in DNA repair (Kohno et al, 2003;Li et al, 2012). Loss of YBX1 is embryonically lethal for mice, resulting in embryos with major CNS malformations (Lu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…YB-1 plays a different role in hepatitis C virus, where its recruitment to sites of virus assembly influences the balance between viral RNA replication and encapsidation (85). Recently, it was reported that YB-1 stabilizes intracellular levels of HIV-1 and murine leukemia virus RNAs, resulting in an increase in virus particle production (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Although YB-1 moves into stress granules during cellular stress, it is also a component of P bodies (alternatively called GW bodies) (17,34); therefore small YB-1 RNPs are constitutive and play a central role in mRNA utilization in nonstressed cells (35). Although YB-1 does have antiviral activity in some RNA viruses (36), the retroviruses HIV-1 and murine leukemia virus (MLV) were recently reported to utilize YB-1 to stabilize viral RNA and increase virus production (37,38).…”
mentioning
confidence: 99%